1989
DOI: 10.1007/bf00375908
|View full text |Cite
|
Sign up to set email alerts
|

Localization of urokinase-type and tissue-type plasminogen activator mRNA during organogenesis in the mouse

Abstract: Cryostat sections of E8.5 to E9.5 mouse embryos were hybridized with S-labelled RNA probes to urokinase-type and tissue-type plasminogen activator (uPA and tPA, respectively) mRNA. The sections were screened for expression of either gene. Two main features emerge from the results. (a) The stage of initial detection is different for each transcript. The uPA mRNA is first detected in cephalic mesenchyme at E8.5 when tPA mRNA is already widely distributed in tissues derived from ectoderm and mesoderm; later, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Plasminogen and its activators are associated with cell migration and tissue remodelling in processes such as neurogenesis and organogenesis, although the developmental expression is complex and not restricted to ectoderm-derived tissues (Moonen et al 1982;Menoud et al 1989;Sumi et al 1992). HGF is also expressed in a complex and changing pattern during development in neural, epithelial and mesodermal tissues, and has both mitogenic and cell scattering properties (reviewed in Warn 1994;Bronner-Fraser 1995).…”
Section: Discussionmentioning
confidence: 96%
“…Plasminogen and its activators are associated with cell migration and tissue remodelling in processes such as neurogenesis and organogenesis, although the developmental expression is complex and not restricted to ectoderm-derived tissues (Moonen et al 1982;Menoud et al 1989;Sumi et al 1992). HGF is also expressed in a complex and changing pattern during development in neural, epithelial and mesodermal tissues, and has both mitogenic and cell scattering properties (reviewed in Warn 1994;Bronner-Fraser 1995).…”
Section: Discussionmentioning
confidence: 96%
“…The exact nature of this role needs to be further examined by delineation and identification of the ligands being bound. Apo E and lipoprotein lipase are not very likely to be necessary ligands, at least not for embryonic development, since mice homozygous for the disrupted apo E gene appear healthy [43] and humans who lack both copies of the gene for lipoprotein lipase develop normal-Other candidates are the tissue and urokinase plasminogen activators, which are expressed in the embryo during the first half of gestation [37,481. It needs to be demonstrated whether also PA11 is expressed during this period, since only tPA-or uPA-PA11 complexes are effectively recognized by the a,MR [40, 411.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been provided that the plasminogen system might be involved in brain function. Fibrinolytic system components are expressed in specialized areas of the brain during development 112 or in adulthood following different forms of brain activity. 113,114 In addition, in vitro studies with cultured neurons revealed that these cells are able to produce and respond to plasminogen activators.…”
Section: Brain Functionmentioning
confidence: 99%